2017
DOI: 10.1186/s13075-017-1337-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine signals are crucial for enhanced homing and differentiation of circulating osteoclast progenitor cells

Abstract: BackgroundThe peripheral blood (PB) monocyte pool contains osteoclast progenitors (OCPs), which contribute to osteoresorption in inflammatory arthritides and are influenced by the cytokine and chemokine milieu. We aimed to define the importance of chemokine signals for migration and activation of OCPs in rheumatoid arthritis (RA) and psoriatic arthritis (PsA).MethodsPB and, when applicable, synovial fluid (SF) samples were collected from 129 patients with RA, 53 patients with PsA, and 110 control patients in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 44 publications
(63 reference statements)
0
51
0
Order By: Relevance
“…Results are shown at week 24 (a) and week 52 (b). CDAI, Clinical Disease Activity Index; HDA, high disease activity; IV, intravenous; LDA, low disease activity; ModDA, moderate disease activity; PsA, psoriatic arthritis; SD, standard deviation; SHS, -Sharp/van der Heijde score OCP populations correlated with peripheral blood TNFα levels [37]. Thus, observations to date suggest TNFα is pivotal in promoting OCP formation.…”
Section: Discussionmentioning
confidence: 96%
“…Results are shown at week 24 (a) and week 52 (b). CDAI, Clinical Disease Activity Index; HDA, high disease activity; IV, intravenous; LDA, low disease activity; ModDA, moderate disease activity; PsA, psoriatic arthritis; SD, standard deviation; SHS, -Sharp/van der Heijde score OCP populations correlated with peripheral blood TNFα levels [37]. Thus, observations to date suggest TNFα is pivotal in promoting OCP formation.…”
Section: Discussionmentioning
confidence: 96%
“… 29 With regard to CXCL10’s role in osteoclast recruitment, a recent report shows that chemokine signals are crucial for enhanced homing and differentiation of circulating osteoclast progenitor cells. 10 The study identified distinct effects of selected chemokines on the stimulation of osteoclast progenitor cell mobilization, tissue homing, and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine CXCL10, also known as IP-10, appears to have a direct influence on osteoclastogenesis for its involvement in leukocyte and osteoclast precursor diapedesis 10 and subsequent presence in the periodontal environment. CXCL10 is a 10 kDa protein and functionally categorized as an “inflammatory” chemokine.…”
Section: Introductionmentioning
confidence: 99%
“…48 RA patients exhibit increased levels of CCL2, CCL3, CCL4, and CXCL10 in plasma as well as synovial fluid. [49][50][51][52][53] On the other hand, CCL5 showed an increased level in the plasma but a reduction in synovial fluid of RA patients. 49 CCL2 is a potent chemoattractant for macrophages, while CCL3 recruits various lymphocytes, monocytes, and eosinophils.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 93%
“…[49][50][51][52][53] On the other hand, CCL5 showed an increased level in the plasma but a reduction in synovial fluid of RA patients. 49 CCL2 is a potent chemoattractant for macrophages, while CCL3 recruits various lymphocytes, monocytes, and eosinophils. 54 Elevated CCL2 level in RA has been strongly associated with an increase in joint infiltration by immune cells, specifically macrophages.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 93%